2023
DOI: 10.2147/amep.s404461
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Sudden Shift from Traditional to Virtual Problem-Based Learning During COVID-19 Pandemic at a Medical College in Saudi Arabia

Abstract: Background COVID-19 pandemic has resulted in a sudden shift to online education. PBL was one of the components that was transformed to online. The aim of the present study was to investigate the impact of the sudden shift to virtual PBL during COVID-19 pandemic in achieving the intended learning objectives of the PBL and to explore the students’ perception of the virtual versus traditional PBL. Methods This is a retrospective study that was conducted in the college of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
1
1
Order By: Relevance
“…While in the present study, there was a split decision regarding their preferred mode of delivery, others have reported that the majority of students showed increased satisfaction online [2,8,18]. Some students indicated that one of the reasons for preferring online PBL is that it saves travel time and cuts down on cost.…”
Section: Preferred Approachcontrasting
confidence: 52%
See 1 more Smart Citation
“…While in the present study, there was a split decision regarding their preferred mode of delivery, others have reported that the majority of students showed increased satisfaction online [2,8,18]. Some students indicated that one of the reasons for preferring online PBL is that it saves travel time and cuts down on cost.…”
Section: Preferred Approachcontrasting
confidence: 52%
“…Still, other students indicated that their learning was disrupted by online delivery [6]. In studies where knowledge was evaluated, and with the exception of one study that showed lower performance of online PBL on learning outcomes [14], they either found no difference in the performance of students in online PBL or a moderate improvement [2,5,8,18,19]. In regards to skills, in a study by Foo et al (2021), tutors assessed student PBL performance (participation, communication, preparation, critical thinking, and group skills) and found that the distance learning group performed statistically lower, although the difference was small (by 0.21-0.42 points on a scale from 0-10) [20].…”
Section: Learning and Assessmentmentioning
confidence: 99%